Factors Affecting the Farmers’ Adoption of Commercial Rice Production in Savannakhet Province, Laos - Chanthavong, Inta; Nilawonk, Weena; Kongtanajaruarun, Rapassorn; Areesrisom, Pawinee; Muakyod, Pinnapa (Journal of Applied Economics and Management Strategy, 2023)
This study aimed to investigate: 1) a level of commercial rice production adoption of the farmers, and 2) factors affecting the farmers adoption of commercial rice production. The respondents in this study consisted of 177 rice farmers gained by the computation of Yamane’s formula (Yamane, 1973). A set of questionnaires was used for data collection and analyzed using descriptive statistics and multiple linear regression was applied to find the factors affecting the adoption of commercial rice production. The study results showed that the farmers had a high level of the adoption of commercial rice production. Based on its detail, two aspects were found at a highest level: preparation of production area and cultivation. However, the other two aspects were found at a high level: maintenance practice and harvest and post-harvest management. In addition, it also found that annual family income, group membership, agricultural training/educational trip, exposure to media, and knowledge/understanding of rice production had a significant positive relationship with the adoption of commercial rice production at a statistical significance level of 0.01 and 0.05. Moreover, to support commercial rice production, the concerned organization should promote the empowerment of elderly farmers by organize agricultural training or study visit, develop irrigation, adding value to rice production under the food safety system, expansion of commercial planting area, increasing channels for receiving agricultural information; and develop domestic and international rice market. These changes would help achieve the government policy to promote commercial rice production around the country for food security, food safety and poverty reduction.